Conducta Obstétrica en primigesta de 20 años de edad en puerperio fisiológico ante hemorragia postparto. - Vélez Espín, Karolyn Stefany (2021)
Postpartum Hemorrhage (PPH) is and has become, throughout obstetric history, one of the main alterations that in many cases prevent leading to an adequate reestablishment of physiological conditions once labor and the subsequent puerperium have concluded, there are multiple etiologies that converge, for the production of the same we have, an alteration of uterine tone, tear during the process of childbirth or cesarean section, retention of placental tissue among those that are considered of greater relevance and importance. To determine hemorrhage after delivery we have to establish that blood loss must exceed 500 ml in a vaginal delivery, and 1000 ml in a cesarean delivery, this establishes the possible presentation of dystocia or multiple pregnancies, which may alter labor delivery and make the appropriate decision, what would be the proper management of such work; for which we have an effective tool to greatly reduce the rates of this alteration, such as active management of the third stage of labor (MATEP). Active management of the third stage of labor (MATEP) refers to the procedures and maneuvers that help to avoid the presentation of postpartum hemorrhage, which are described herein, remembering that postpartum hemorrhage is considered as such at the time understood between the first 24 hours after childbirth, up to 6 weeks after it. CLINICAL CASE: A 20-year-old patient, with a 39.4-week pregnancy diagnosed by LMP, with no previous relevant pathologies, both personal and family, with poor controls. The patient in this present study underwent only one control during the entire pregnancy; therefore, it is considered deficient according to the 2013 MSP guide since it says that there must be a minimum of 5 check-ups, first pregnancy, without previous abortions or cesarean sections.